Monte Carlo simulation of an HPGe detector for detection of 239Pu in waste assay system. (October 2019) - Pavan Narayanam, Sujatha; Manohari, M.; Ramar, R.; Subramanian, V.; Mathiyarasu, R.; Srinivas, C.V.; Baskaran, R.
Abstract: This paper discusses the modeling of HPGe detector used in waste assay system using Monte Carlo code FLUKA to determine its detection limits. The modeled detector is validated using experimental point sources efficiencies in the energy range 60 keV–2000 keV. The numerical estimation of efficiency values for 239 Pu present inside a 230 L cotton filled waste drum at various locations along the axis of the detector is discussed. Estimation of the minimum detectable activity (MDA) for 239 Pu at these locations in the presence of 1 MBq of 137 Cs/ 60 Co again along the axis of the detector is examined. The efficiency of 239 Pu decreases from 6.1 × 10 -10 to 7.5 × 10 -11 cps/Bq as the location of 239 Pu moves away from the detector. MDA of 239 Pu increases as the position of 239 Pu and 137 Cs/ 60 Co in the waste drum shifts away from the detector while it decreases as the location of 137 Cs/ 60 CO moves away from 239 Pu along measurement axis. It is observed that for all locations of 137 Cs/ 60 Co with 239 Pu located up to 200 mm from the edge of the drum, the detection limit is within 140.3 mg (allowed limit). Highlights: Validation of HPGe detector model by comparison of simulated efficiencies with the experimental ones for point sources. Simulation of waste assay system using Monte Carlo code FLUKA and validation of model. Determination of the detection efficiency of HPGe detector in waste assay system within energy range 60 to 2000 keV. Estimation of MDA of 239 Pu in the presence of 137 Cs/ 60 Co at various locations along the measurement axis of the waste drum.